The TGF-β1 Signaling Pathway as an Attractive Target in the Fibrosis Pathogenesis of Sjögren’s Syndrome - Sisto, Margherita; Lorusso, Loredana; Ingravallo, Giuseppe; Tamma, Roberto; Ribatti, Domenico; Lisi, Sabrina (Mediators of Inflammation, 2018)
Transforming growth factor β1 (TGF-β1) plays a crucial role in the induction of fibrosis, often associated with chronic phases of inflammatory diseases contributing to marked fibrotic changes that compromise normal organ function. The TGF-β1 signal exerts its biological effects via the TGF-β/SMAD/Snail signaling pathway, playing an important pathogenic role in several fibrotic diseases. It has as yet been poorly investigated in the chronic autoimmune disease Sjögren’s syndrome (SS). Here, we firstly tested, by immunohistochemistry, whether the TGF-β1/SMAD/Snail signaling pathway is triggered in human pSS salivary glands (SGs). Next, healthy salivary gland epithelial cell (SGEC) cultures derived from healthy donors were exposed to TGF-β1 treatment, and the relative gene and protein levels of SMAD2/3/4, Snail, E-cadherin, vimentin, and collagen type I were compared by semiquantitative RT-PCR, quantitative real-time PCR, and Western blot analysis. We observed, both at gene and protein levels, higher expression of SMAD2, 3, and 4 and Snail in the SGEC exposed by TGF-β1 compared to untreated healthy SGEC. Additionally, in TGF-β1-treated samples, we found a significant reduction in the epithelial phenotype marker E-cadherin and an increase in the mesenchymal phenotype markers vimentin and collagen type I compared to those in untreated SGEC, indicating that TGF-β1 induces the EMT via the TGF-β1/SMAD/Snail signaling pathway. Therefore, by using the specific TGF-β receptor 1 inhibitor SB-431542 in healthy SGEC treated with TGF-β1, we showed a significant reduction of the fibrosis markers vimentin and collagen type I while the epithelial marker E-cadherin returns to levels similar to untreated healthy SGEC. These data demonstrate that TGF-β1 is an important key factor in the transition phase from SG chronic inflammation to fibrotic disease. Characteristic changes in the morphology and function of TGF-β1-treated healthy SGEC further confirm that TGF-β1 plays a significant role in EMT-dependent fibrosis.